2020
DOI: 10.3390/su12030775
|View full text |Cite
|
Sign up to set email alerts
|

Social Trust and Open Innovation in an Informal Economy: The Emergence of Shenzhen Mobile Phone Industry

Abstract: This study examines how social trust facilitates firms’ collaborative efficiency in an informal economy. We extend the open innovation theory to explain the straightforward role of social trust in the Shenzhen mobile phone industry. This single case study yields two principal findings. First, social trust fosters the efficient integration of value chains for mobile phone development. Four types of informal entrepreneurs with high social trust built on homogenous sanctioned ethnic groups (i.e., Fujian, Hunan, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 81 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…The 21st paper analyzes how technology start-ups increase innovative performance, with a focus on employment change in Korea, which is related to entrepreneur leading culture for open innovation dynamics, in addition to manufacturing firms in Southeast Asia [141,142].…”
Section: Organizational Entrepreneurship Leading Culture For Open Innovation Dynamicsmentioning
confidence: 99%
“…The 21st paper analyzes how technology start-ups increase innovative performance, with a focus on employment change in Korea, which is related to entrepreneur leading culture for open innovation dynamics, in addition to manufacturing firms in Southeast Asia [141,142].…”
Section: Organizational Entrepreneurship Leading Culture For Open Innovation Dynamicsmentioning
confidence: 99%
“…So far, the role of open innovation in the informal economy has not gained much attention in extant literature. In [90], the authors reported that informal cultural norms such as social trust or ties can improve open innovation outputs when explored by an informal economy as demonstrated by the Shenzhen mobile industry in China. The potential for open innovation in the informal economy was also substantiated by observed practices among informal sector auto parts fabricators in Kampala, Uganda as reported in [91,92].…”
Section: Open Innovation In the Informal Sector For Economic Growthmentioning
confidence: 99%
“…The informal economy, also known as the hidden, underground, black, grey, shadow, irregular, or unobserved economy, is increasingly gaining traction among researchers (Khuong et al, 2020). Partly, this is due to the significant economic role played by informal businesses (Y. C. Chen & Chen, 2020;Lv, 2020). For instance, the International Labour Organization [ILO] (2020) noted that two billion people, equivalent to 61.2% of the world's employed individuals, worked in the informal economy.…”
Section: Introductionmentioning
confidence: 99%